Performance comparison between retailing stores using a Malmquist-type index - Vaz, Clara B. (2010)
This study develops a framework that combines different methods to provide insights regarding the performance of retailing stores. Firstly, the framework enables to specify appropriate targets for stores using DEA. This involves comparing stores within homogeneous groups. Secondly, the framework compares the overall performance of these groups. This requires the combined use of Malmquist type index and statistical tests. This index is decomposed into components for comparing the efficiency spread between groups and the productivity differences between the best-practice frontiers of the groups.